Evaluation of an mHealth intervention aiming to improve health-related behavior and sleep and reduce fatigue among airline pilots - van Drongelen, Alwin; Boot, Cécile RL; Hlobil, Hynek; Twisk, Jos WR; Smid, Tjabe; van der Beek, Allard J. (Scandinavian Journal of Work, Environment & Health, 2014)
' ' OBJECTIVES ': 'The aim of this study was to evaluate the effects of an mHealth intervention (intervention using mobile technology) consisting of tailored advice regarding exposure to daylight, sleep, physical activity, and nutrition, and aiming to improve health-related behavior, thereby reducing sleep problems and fatigue and improving health perception of airline pilots. ' ' METHODS ': 'A randomized controlled trial was conducted among 502 airline pilots. The intervention group was given access to both the MORE Energy mobile application (app) with tailored advice and a website with background information. The control group was directed to a website with standard information about fatigue. Health-related behavior, fatigue, sleep, and health perception outcomes were measured through online questionnaires at baseline and at three and six months after baseline. The effectiveness of the intervention was determined using linear and Poisson mixed model analyses. ' ' RESULTS ': 'After six months, compared to the control group, the intervention group showed a significant improvement on fatigue (β= -3.76, P<0.001), sleep quality (β= -0.59, P=0.007), strenuous physical activity (β=0.17, P=0.028), and snacking behavior (β= -0.81, P<0.001). No significant effects were found for other outcome measures. ' ' CONCLUSIONS ': 'The MORE Energy mHealth intervention reduced self-reported fatigue compared to a minimal intervention. Some aspects of health-related behavior (physical activity and snacking behavior) and sleep (sleep quality) improved as well, but most did not. The results show offering tailored advice through an mHealth intervention is an effective means to support employees who have to cope with irregular flight schedules and circadian disruption. This kind of intervention might therefore also be beneficial for other working populations with irregular working hours.
Keywords: airline pilot; circadian disruption; education; evaluation; fatigue; flight crew; health-related behavior; intervention; mHealth; mobile health; pilot; sleep; work schedule tolerance